THE LEVEL OF ACHIEVEMENT ABILITIES IN THE CURRICULUM SUBJECT AND TEACHING METHODS FOR STUDENTS OF THE FACULTY OF EDUCATION - Al-Janabi, Ahlam hameed; Sahib Mussa, AL.zuwainy Ibtisam (International Journal of Psychosocial Rehabilitation, 2020)
The current research goal is to know the level of achievement abilities and then use the descriptive method in the investigation from the research tool to test the achievement abilities with dimensions (the cognitive aspect and the skill side) and the results concluded that there are no statistically significant differences between education students in the light of the results and then reach A number of recommendations.